Relire les rites dans Vendredi ou les Limbes du Pacifique de Michel Tournier dans le contexte de la décolonisation - Masłowski, Damian (Romanica Silesiana)
The purpose of this paper is to focus on the extraliterary function of the rites performed on Speranza Island by Robinson Crusoe — a colonizer — and by Friday who represents the Third World. Such investigation is relevant because Michel Tournier’s Friday, or, The Other Island is a postcolonial transvalorization of the classic Robinsonade, in which the author inverts the classic story first published in 1719. In Tournier’s case, owing to the repetitiveness and cyclicity of everyday activities, it is possible to read the rites as an allegoric image of crucial processes — such as language teaching or getting married — taking place in the colonial and postcolonial world of Algeria. The rites in Tournier’s novel are also considered to be a symbolic attempt to establish new relationships between French colonizers and African colonized society, who both witnessed the process of decolonization in the twentieth century. Key words: Robinson Crusoe, Friday, colonialism, postcolonialism, rite, Algeria, decolonization